Some aspects of cell therapy and stem cells - S. V. Jargin (Сибирский научный медицинский журнал, 2021)
Numerous publications on stem cells and cell therapies have appeared last time. Topics discussed in the literature include the differentiation of exogenous SC into various cell lineages, the replacement of senescent, dysfunctional, and damaged cells. However, in vitro differentiation with the expression of certain markers does not prove replacement of functioning cells in vivo. The application of cell therapies in cardiovascular, hepatic, neurodegenerative diseases, osteoarthritis and diabetes mellitus is discussed in this article. Recent data on COVID-19 are overviewed. Some publications exaggerate successes of cell therapies without giving due consideration to potential adverse effects. In recent years there has been a global expansion of stem cell treatments. In conclusion, therapeutic methods with unproven effects should be applied within the framework of high-quality scientific research shielded from conflicts of interest.